Protective effect of prostacyclin against pre-cardiac edema caused by 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin and a thromboxane receptor agonist in developing zebrafish. (August 2016) - Nijoukubo, Daisuke; Tanaka, Yasuaki; Okuno, Yuki; Yin, Guojun; Kitazawa, Takio; Peterson, Richard E.; Kubota, Akira; Teraoka, Hiroki
Abstract: The role of prostaglandin pathways has been suggested in some toxicological responses to dioxins. Cyclooxygenase type 2b (COX2b), thromboxane synthase, and the thromboxane receptor (TP) pathway have been implicated in mediating 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD)-induced pre-cardiac edema in developing zebrafish at 55 h post fertilization (hpf). Pre-cardiac edema refers to edema located in a small cavity between the heart and body wall of zebrafish eleutheroembryos. In the present study, we assessed the role of prostacyclin, which counteracts some biological effects of thromboxane, in TCDD-induced pre-cardiac edema. Pre-cardiac edema induced by TCDD exposure (0.5 and 1 ppb) beginning at 24 hpf was markedly inhibited by exposure to beraprost (5 and 10 μM), a prostacyclin receptor (IP) agonist, beginning at 33 hpf. The preventive effect of beraprost was reduced by exposure to CAY10441 (10 μM), an IP antagonist starting at 33 hpf. Knockdowns of the IP receptor (IP-KD) with two different morpholinos caused edema by themselves and enhanced pre-cardiac edema caused by the low concentration of TCDD (0.5 ppb). On the other hand, short exposure beginning at 48 hpf to U46619 (7.5–30 μM), a thromboxane receptor agonist caused pre-cardiac edema, which was inhibited by exposure beginning at 48 hpf to both ICI-192, 605 (24 μM), a TP antagonist, and beraprost. Expression of prostacyclin synthase was increased from fertilization, plateaued by 48 hpf, and was maintained until at least 96 hpf. Overall, the results demonstrate a preventive effect of prostacyclin on TCDD-induced pre-cardiac edema in developing zebrafish. Highlights: TCDD and thromboxane receptor (TP) agonist cause pre-cardiac edema in zebrafish. A prostacyclin receptor (IP) agonist inhibits TCDD- and TP agonist-induced edema. On the other hand, IP inhibition causes pre-cardiac edema in zebrafish embryos. IP inhibition enhances the minimal pre-cardiac edema caused by a low dose of TCDD.